2015
DOI: 10.1590/0104-1428.1694
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção de micro e nanofibras de PVC pela técnica de Fiação por Sopro em Solução

Abstract: Neste trabalho, micro e nanofibras de PVC foram obtidas pela técnica de Fiação por Sopro em Solução, uma técnica recentemente desenvolvida capaz de produzir micro e nanoestruturas poliméricas com velocidade alta e preços que rivalizam a eletrofiação. As micro e nanofibras produzidas neste trabalho, a partir de soluções de PVC em tetrahidrofurano tiveram diâmetros médios entre 217 nm e 2,5 μm. Os efeitos das condições de processamento foram avaliados, sendo que a concentração da solução polimérica foi o parâmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
3
0
9
Order By: Relevance
“…Limonene has been used to produce PS nanofibers by electrospinning, but to the best of our knowledge this is the first time it has been used by solution blow spinning, an alternative to other fiber‐forming technique, including electrospinning, to produce microfiber and nanofiber of polymers and ceramics due to advantages such as larger production rates and reduced costs . Furthermore, solution blow spun (SBS) requires a rather simple apparatus by replacing high voltage with a pressurized source of gas exiting a specially designed nozzle, through which a polymer can be injected to form fibers that are drawn by aerodynamic forces toward the collector, which can be a rotating drum, a living tissue, or any collecting system . Previous studies have reported the use of nanofibrous mats of electrospun nanofibers of PS as sorbents for the extraction of polar compounds, determination of nicotine in cigarettes, and filtration media…”
Section: Introductionmentioning
confidence: 99%
“…Limonene has been used to produce PS nanofibers by electrospinning, but to the best of our knowledge this is the first time it has been used by solution blow spinning, an alternative to other fiber‐forming technique, including electrospinning, to produce microfiber and nanofiber of polymers and ceramics due to advantages such as larger production rates and reduced costs . Furthermore, solution blow spun (SBS) requires a rather simple apparatus by replacing high voltage with a pressurized source of gas exiting a specially designed nozzle, through which a polymer can be injected to form fibers that are drawn by aerodynamic forces toward the collector, which can be a rotating drum, a living tissue, or any collecting system . Previous studies have reported the use of nanofibrous mats of electrospun nanofibers of PS as sorbents for the extraction of polar compounds, determination of nicotine in cigarettes, and filtration media…”
Section: Introductionmentioning
confidence: 99%
“…Existem poucas técnicas conhecidas na literatura, que são capazes de produzir fi bras de óxidos cerâmicos em tamanho nanométrico, destacando-se a eletrofi ação (EF) e a fi ação por sopro em solução (Solution Blow Spinning -SBS), esta segunda, desenvolvida nos últimos 10 anos. A priori, a utilização desse método mostrou-se efi ciente para a produção de nanofibras poliméricas (MEDEIROS et al, 2009;OLIVEIRA et al, 2011a;OLIVEIRA et al, 2011b;OLIVEIRA et al, 2012;TEÓFILO et al, 2014;SILVA et al, 2015) e recentemente nanofibras cerâmicas, de mulita e sílica (FARIAS et al, 2015;TEIXEIRA et al, 2016). Destaca-se ainda a diferença no que diz respeito ao volume de produção, enquanto na eletrofiação a produção média é de 3 mL por hora, a fiação por sopro em solução possui taxa de produção de 45ml por hora (WOJASI et al, 2011).…”
Section: Introductionunclassified
“…Com o avanço das pesquisas em nanocompósitos, em que a fase dispersa deve ter pelo menos uma das dimensões inferiores a 1000 nm (SASIPRYIA et al, 2013), diversas cargas já se mostraram viáveis para aplicação, como nanopartículas (ASSIS, 2012), nanotubos de carbono (SALES, 2013), nanoesferas (CAIADO, 2014) e as próprias nanofibras (PLOTEGHER; RIBEIRO, 2013). Devido à elevada razão de aspecto, associada a uma elevada área superficial específica, as nanofibras têm mostrado grandes potenciais de aplicação como sensores ópticos eletrônicos, biosensores, matrizes para a imobilização de catalisadores, reforços estruturais, filtros capazes de reter microorganismos e partículas sólidas extremamente finas de líquidos ou gases, substratos para crescimento de órgãos e tecidos biológicos, encapsulação e liberação controlada de fármacos, curativo para a regeneração da pele, entre outros (HUANG et al, 2003;AUSSAWASATHIENA et al, 2005;MA et al, 2005;PHAN et al, 2006;GOPAL et al, 2006;MARTINS et al, 2007;VELEIRINHO et al, 2009;OLIVEIRA, 2011;COSTA et al, 2012;ZADOROSNY, 2013;VALENTE, 2014;SILVA et al, 2015).…”
Section: Introductionunclassified